Diospyros kaki Thunb. and its Hybrids with D. virginiana L. in АR Crimea’s Moderately Warm Areas: Overwintering Results in 2005-2006 (CHORNOMORSKI BOTANICAL JOURNAL, 2006)
The results of overwintering (2005-2006) Diospyros kaki Trunm. and its hybrids with D. virginiana L. in some Crimia’s moderately warm areas are elucidated.
Keywords: persimmon, hybrids, overwintering, Crimea.